(untitled) (Literary Voice, 2023)
In several works by Margaret Atwood, food is a metaphor for power. The powerful ones eat and the weak counterparts do not. Power is latent under the acts of consumption in daily life basic survival acts. The paper discusses aspects mentioned about food in Atwood’s novels, notably feminist ideas of eating disorders that invite intriguing significations regarding the food motif. The analysis of the politics of eating in her works within the framework of Foucauldian discourse overlapping with Gramscian hegemonic economy, offers a fresh perspective on women’s subverted position attributed to food.